Resin composition and manufacturing method thereof and substrate structure
The resin composition, comprising hydrocarbon resin polymer and divinyl aromatic compound, addresses the issues of smoke and solvent use in existing resin compositions by enabling crosslinking at lower temperatures or shorter times, resulting in a more environmentally friendly, cost-effective, and high-performance material.
Patent Information
- Application Number
- JP2024139708
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2024-07-29
- Filing Date
- 2024-08-21
- Publication Date
- 2025-03-18
AI Technical Summary
The existing resin compositions used in copper-clad laminates and integrated circuit carriers require triallyl isocyanurate as a crosslinking agent, which causes smoke and thermal decomposition during high-temperature processing, and also rely on organic solvents for purification, leading to environmental and cost issues.
A resin composition comprising 100 parts by weight of hydrocarbon resin polymer and 0.01 to 50 parts by weight of divinyl aromatic compound, which allows for crosslinking without the need for triallyl isocyanurate and can be processed at lower temperatures or shorter times, and may reduce or eliminate the use of organic solvents.
The proposed resin composition achieves crosslinking at lower temperatures or shorter times, reducing energy consumption and eliminating smoke production, while also being environmentally friendly and cost-effective, with improved thermal and electrical properties.
Smart Images

Figure 2025037818000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of U.S. Provisional Application No. 63 / 578,090, filed August 22, 2023, and also claims the benefit of Taiwan Patent Application No. 113,128,082, filed July 29, 2024, the entireties of which are incorporated herein by reference.
[0002] The present disclosure relates to a resin composition, a method for making the resin composition, and a substrate structure including the resin composition. More particularly, the present disclosure relates to a resin composition including a hydrocarbon resin polymer, a method for making the resin composition, and a substrate structure including the resin composition. [Background technology]
[0003] With the rise of cloud, internet, and internet of things (IOT), and the improvement of 5G communication technology and display technology, the requirements for materials used to make circuit boards and integrated circuit carriers (IC carriers) required for optoelectronics, communication, and semiconductor industries are becoming more and more stringent. Copper clad laminate (CCL) is an important material commonly used in electronic products and is mainly used to manufacture circuit boards. Hydrocarbon resin polymers or polyene materials, which are composed of carbon and hydrogen atoms, have low number of polar functional groups and therefore have low dielectric loss properties. Therefore, polymerizable hydrocarbon resin polymers can be used as materials for copper clad laminates or integrated circuit carriers.
[0004] Triallyl isocyanurate (TAIC) is often used as a crosslinking agent to crosslink with various resins (e.g., hydrocarbon resin polymers) to form resin layers in copper-clad laminates. However, the use of triallyl isocyanurate as a crosslinking agent can cause smoke generation. Specifically, the process of manufacturing copper-clad laminates requires a high-temperature process, which can cause thermal decomposition or volatilization (i.e., smoke generation) of triallyl isocyanurate. In addition, during preparation, polymerizable hydrocarbon resin polymers are usually purified using organic solvents. The use of organic solvents is not environmentally friendly and increases costs. Summary of the Invention [Problem to be solved by the invention]
[0005] In view of the above problems, the present disclosure provides a resin composition that does not require triallyl isocyanurate as a crosslinking agent during crosslinking, and / or can be crosslinked at a lower crosslinking temperature or shorter crosslinking time. The resin composition of the present disclosure does not require the use of an organic solvent during preparation, or can reduce the amount of organic solvent. The substrate structure made using the resin composition of the present disclosure can be obtained at low cost, with low energy consumption, and / or in an environmentally friendly manner. In addition, the substrate structure made using the resin composition of the present disclosure can have good thermal properties (e.g., high glass transition temperature, Tg) or good electrical performance. [Means for solving the problem]
[0006] In some embodiments, the present disclosure provides a resin composition comprising 100 parts by weight of a hydrocarbon resin polymer and 0.01 to 50 parts by weight of a divinylaromatic compound.
[0007] In some embodiments, the present disclosure provides a method for making a resin composition, the method including the steps of providing a mixture, the mixture optionally including a bridged ring compound, a monovinyl aromatic compound, and a divinylaromatic compound, polymerizing the mixture to form a crude composition, and purifying the crude composition to prepare a resin composition, the resin composition including 100 parts by weight of a hydrocarbon resin polymer and 0.01 to 50 parts by weight of a divinylaromatic compound.
[0008] In some embodiments, the present disclosure provides a substrate structure, the substrate structure including a resin layer and a conductive layer disposed on the resin layer, the resin layer being formed from a resin composition using a crosslinking process, the resin composition including 100 parts by weight of a hydrocarbon resin polymer and 0.01 to 50 parts by weight of a divinyl aromatic compound. [Brief description of the drawings]
[0009] The embodiments, objects, features and advantages of the present disclosure are best understood in conjunction with the accompanying drawings in conjunction with the following detailed description. [Figure 1] 1 is a flow chart of a method for making a resin composition according to some embodiments of the present disclosure. [Diagram 2] 1 is a schematic diagram of a substrate structure according to some embodiments of the present disclosure. [Diagram 3] 1 is a graph showing the relationship between storage modulus and loss modulus and temperature for a resin composition according to some embodiments. [Figure 4] 1 is a graph showing storage modulus and loss modulus versus time for a resin composition according to some embodiments. [Diagram 5] 1 is a graph showing the complex viscosity versus time of a resin composition according to some embodiments. [Figure 6] 1 is a graph showing the relationship between the glass transition temperature of substrate samples of resin compositions and the DVB content in the resin compositions, according to some embodiments of the present disclosure. [Figure 7]1 is a graph showing the relationship between resin flow of substrate samples of resin compositions and DVB content in the resin compositions, according to some embodiments of the present disclosure. [Figure 8] 1 is a graph showing the relationship between loss tangent (Df) of substrate samples of a resin composition and the DVB / TAIC content in the resin composition according to some embodiments of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] It is further understood that, as used herein, the terms "comprises" and / or "includes" specify the presence of stated features, integers, steps, operations, elements, components and / or groups thereof, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or groups thereof. As used herein, the singular forms "a," "an," and "the" are intended to encompass the plural forms unless the context clearly indicates otherwise.
[0011] It is understood that the terms "first," "second," and the like are used herein to describe various elements, components, regions, layers, and / or sections, and that these elements, components, regions, layers, and / or sections are not to be limited by these terms. These terms are used to distinguish one element, component, region, layer, or section from another element, component, region, layer, or section, but do not imply a necessary order of the components.
[0012] As used herein, the terms "about", "approximately" and "roughly" primarily refer to a given value or range of values that vary within 20%, preferably within 10%, preferably within 5%, or within 3%, or within 2%, or within 1%, or within 0.5%. The given values are approximate values, that is, unless otherwise specified, the meanings of "about", "approximately" and "roughly" may be included. It is further understood that the numerical values shown in this specification may include those numerical values and deviation values within the deviation range acceptable to those having ordinary skill in the art. It is understood that the expression "a to b" used in this specification to indicate a range of a particular value is defined as "≧a and ≦b".
[0013] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. Terms defined in commonly used dictionaries should be interpreted to have a meaning consistent with the relevant technology, context or background of the present disclosure, and should not be interpreted in an idealized or overly formal sense unless clearly defined in the present specification. Hereinafter, descriptions of known functions and structures that may unnecessarily obscure the present disclosure will be omitted.
[0014] As used herein, the term "C 1-20 "Alkyl group" refers to a monovalent radical of a linear, branched, or cyclic aliphatic hydrocarbon having from 1 to 20 carbon atoms in the carbon chain. 1-20 Examples of alkyl groups include, but are not limited to, methyl, ethyl, propyl, iso-butyl, sec-butyl, tert-butyl, pentyl, iso-amyl, hexyl, decyl, dodecyl, cyclohexyl, cyclooctyl, and cyclododecyl groups.
[0015] As used herein, the term "C 2-20An "alkenyl group" refers to a monovalent group of linear, branched, or cyclic aliphatic hydrocarbons having from 2 to 20 carbon atoms in the carbon chain and at least one carbon-carbon double bond. 2-20 Examples of alkenyl groups include, but are not limited to, ethenyl, propenyl, isobutenyl, sec-butenyl, tert-butenyl, pentenyl, isopentenyl, hexenyl, decenyl, dodecenyl, pentadecenyl, cyclohexenyl, cyclooctenyl, cyclopentenyl, cyclopentadienyl, and cyclopentadecenyl groups.
[0016] As used herein, the term "bridged ring compound" refers to a compound that contains a bridged ring structure. A bridged ring structure refers to a compound that contains at least two carbon rings that share two carbon atoms that are not directly linked. Examples of bridged ring compounds include, but are not limited to, the following:
[0017] [ka]
[0018] Some embodiments of the present disclosure provide a resin composition. The resin composition includes 100 parts by weight of a hydrocarbon resin polymer and 0.01 to 50 parts by weight of a divinylaromatic compound. The hydrocarbon resin polymer in the resin composition of the present disclosure includes cross-linkable groups. In some embodiments, the cross-linkable groups may include unsaturated groups, epoxy groups, or hydroxyl groups, or combinations thereof, but the present disclosure is not limited thereto. In some embodiments, the resin composition of the present disclosure includes more than 0.01 parts by weight of a divinylaromatic compound, allowing the resin composition of the present disclosure to be cross-linked without the addition of an additional cross-linking agent. The resin composition of the present disclosure includes less than 50 parts by weight of a divinylaromatic compound, allowing the resin composition of the present disclosure to have a suitable viscosity, which provides excellent processability. In some embodiments, the resin composition of the present disclosure may include 0.1 to 48 parts by weight, 0.2 to 45 parts by weight, or 0.4 to 43 parts by weight of a divinylaromatic compound, based on 100 parts by weight of the hydrocarbon resin polymer.
[0019] The storage modulus of the resin composition of the present disclosure exceeds the loss modulus at about 125°C to 165°C. In other words, the resin composition of the present disclosure has solid properties that exceed those of a liquid within a temperature range of about 125°C to 165°C, which indicates that the crosslinking temperature of the resin composition is within this temperature range. A detailed method for measuring the crosslinkable temperature will be described later. The crosslinkable temperature of the resin composition of the present disclosure is about 125°C to 165°C. In some embodiments, the crosslinkable temperature of the resin composition may be about 135°C to 163°C or 135°C to 160°C. In some embodiments, the crosslinkable temperature of the resin composition may be about 140°C to 155°C. The lower the crosslinkable temperature, the lower the crosslinking temperature of the resin composition, which indicates that the crosslinking process can be performed at a lower crosslinking temperature, thereby reducing the energy required during the crosslinking process.
[0020] The resin composition of the present disclosure may have a storage modulus of about 10,000 to 10,000,000 Pa after a crosslinking temperature of 160° C. and a crosslinking time of 2000 seconds. In some embodiments, the storage modulus of the resin composition after a crosslinking temperature of 160° C. and a crosslinking time of 2000 seconds is about 20,000 to 9,000,000 Pa or 21,000 to 8,500,000 Pa. In some embodiments, the storage modulus of the resin composition after a crosslinking temperature of 160° C. and a crosslinking time of 2000 seconds is about 100,000 to 2,000,000 Pa or 200,000 to 1,000,000 Pa.
[0021] The crosslinking time corresponding to the storage modulus obtained by multiplying the storage modulus obtained by proceeding with crosslinking of the resin composition at a crosslinking temperature of 160° C. for a crosslinking time of 2000 seconds by 0.9 is defined as the “required crosslinking time”. In some embodiments, the “required crosslinking time” of the resin composition of the present disclosure is about 1300 to 1900 seconds, which means that the resin composition of the present disclosure can be substantially crosslinked after a crosslinking time of about 1300 to 1900 seconds. In some embodiments, the “required crosslinking time” of the resin composition of the present disclosure is about 1700 to 1850 seconds.
[0022] The resin composition of the present disclosure has a complex viscosity of about 1.00×10 after half the “required crosslinking time” has elapsed at a crosslinking temperature of 160° C. 4 From 6.00 x 10 8 cP, e.g., 1.00 x 10 6 to 1.00 x 10 8 cP, 1.00×10 7 to 1.00 x 10 8 cP, 1.00×10 7 From 5.00 x 10 7 It may be cP.
[0023] In some embodiments, the hydrocarbon resin polymer in the resin composition of the present disclosure may include repeat units derived from a monovinyl aromatic compound (B) and repeat units derived from a divinyl aromatic compound (C).
[0024] Here, a monovinyl aromatic compound refers to a compound that contains a carbocyclic aromatic structure, in which one hydrogen atom on a ring carbon atom of the carbocyclic aromatic structure is replaced with a vinyl group. In some embodiments, the vinyl group may be unsubstituted. In some embodiments, at least one hydrogen atom on the vinyl group is replaced with a C 1-20 In some embodiments, the carbocyclic aromatic structure may be substituted with an alkyl group. In some embodiments, the carbocyclic aromatic structure may contain 6 to 60 or 6 to 20 ring carbon atoms. In some embodiments, the carbocyclic aromatic structure may be unsubstituted. In some embodiments, at least one hydrogen on a ring carbon atom in the carbocyclic aromatic structure is C 1-20 The monovinyl aromatic compounds may include, for example, styrene, methylstyrene, or ethylstyrene, but the disclosure is not limited thereto.
[0025] The repeat unit (B) derived from a monovinyl aromatic compound includes a carbocyclic aromatic structure derived from a monovinyl aromatic compound. For example, in some embodiments, the repeat unit (B) may have the following structure, but the disclosure is not limited thereto:
[0026] [ka]
[0027] In the above structures, "*" indicates the position of attachment to other groups or units.
[0028] Here, a divinylaromatic compound refers to a compound that contains a carbocyclic aromatic structure, in which two hydrogen atoms on the ring carbon atoms of the carbocyclic aromatic structure are replaced by vinyl groups. In some embodiments, the vinyl group may be unsubstituted. In some embodiments, at least one hydrogen atom on the vinyl group is replaced by C 1-20In some embodiments, the carbocyclic aromatic structure may be substituted with an alkyl group. In some embodiments, the carbocyclic aromatic structure may contain 6 to 60 or 6 to 20 ring carbon atoms. In some embodiments, the carbocyclic aromatic structure may be unsubstituted. In some embodiments, at least one hydrogen on a ring carbon atom of the carbocyclic aromatic structure is C 1-20 The divinylaromatic compounds may include, for example, divinylbenzene or diisopropenylbenzene, but the disclosure is not limited thereto.
[0029] The repeating unit (C) derived from a divinylaromatic compound comprises a carbocyclic aromatic structure derived from a divinylaromatic compound. In some embodiments, the repeating unit (C) may comprise a cross-linkable repeating unit (C1) and a cross-linked repeating unit (C2).
[0030] [ka]
[0031] R1, R2, R3, and R4 in the crosslinkable repeating unit (C1) and the crosslinking repeating unit (C2) are each independently H or C. 1-20 Ar1 and Ar2 may be alkyl groups, and Ar1 and Ar2 may be phenylene groups. "*" indicates the linking position of the crosslinkable repeat unit (C1) and / or the crosslinking repeat unit (C2) to other groups or units. In some embodiments, the crosslinkable repeat unit (C1) may include the structure shown below, but the disclosure is not limited thereto.
[0032] [ka]
[0033] In some embodiments, the bridging repeat unit (C2) may include the structure shown below, although the disclosure is not limited thereto.
[0034] [ka]
[0035] In some embodiments, the hydrocarbon resin polymer may contain 15 to 95 mol% of repeating units (B) and 5 to 85 mol% of repeating units (C) relative to 100 mol% of the hydrocarbon resin polymer. When the contents of repeating units (B) and repeating units (C) in the hydrocarbon resin polymer are within the above ranges, the hydrocarbon resin polymer may have better thermal properties and / or processability. In some embodiments, the hydrocarbon resin polymer may contain 35 to 94 mol% of repeating units (B) and 6 to 55 mol% of repeating units (C), 45 to 93 mol% of repeating units (B) and 7 to 45 mol% of repeating units (C), or 55 to 92 mol% of repeating units (B) and 8 to 35 mol% of repeating units (C), relative to 100 mol% of the hydrocarbon resin polymer. In some embodiments, the hydrocarbon resin polymer may contain 1 to 30 mol% of crosslinkable repeating units (C1), relative to 100 mol% of the hydrocarbon resin polymer. When the content of the crosslinkable repeating unit (C1) in the hydrocarbon resin polymer is within the above range, the hydrocarbon resin polymer can have better thermal properties, electrical performance and / or processability.
[0036] In some embodiments, the hydrocarbon resin polymer in the resin composition of the present disclosure may further comprise a repeat unit (A) derived from a bridged ring compound. In some embodiments, the bridged ring compound may comprise 3 to 12 ring-forming atoms and 1 to 2 double bonds. In some embodiments, the bridged ring compound may be unsubstituted. In some embodiments, at least one hydrogen atom on the bridged ring compound is C 1-20 Alkyl group, C 2-20 In some embodiments, the bridged ring compound includes at least two substituents, the at least two of which are selected from the group consisting of an alkenyl group, an alkenyl group, or a carboxylate group having a carbon backbone of 1 to 20 carbon atoms. In some embodiments, the bridged ring compound includes at least two substituents, the at least two of which are selected from the group consisting of C 1-20 Alkyl group, C 2-20 The two substituents may be any two selected from the group consisting of an alkenyl group, or a carboxylate group having a carbon backbone of 1 to 20 carbon atoms. Adjacent substituents of at least two of the substituents may form a ring. Examples of bridged ring compounds may include dicyclopentadiene or norbornene, but the disclosure is not limited thereto.
[0037] In some embodiments, the repeat unit (A) may have the following structure, although the disclosure is not limited thereto:
[0038] [ka]
[0039] In the above structure, "*" indicates the position of linkage with other groups or units. Compared with a linear repeating unit, the repeating unit (A) derived from a bridged ring compound has higher rigidity. Therefore, the glass transition temperature of the hydrocarbon resin polymer may be increased, or the thermal properties of the hydrocarbon resin polymer may be improved.
[0040] In some embodiments, the hydrocarbon resin polymer may contain 0.15 to 15 mol% of the repeat unit (A) relative to 100 mol% of the hydrocarbon resin polymer. When the content of the repeat unit (A) in the hydrocarbon resin polymer is within the above range, the thermal properties of the hydrocarbon resin polymer are better and the production cost can be reduced. In some embodiments, the hydrocarbon resin polymer may contain 0.5 to 12 mol%, 1 to 10 mol%, or 1.5 to 8 mol% of the repeat unit (A) relative to 100 mol% of the hydrocarbon resin polymer.
[0041] In some embodiments, the total content of repeating units (A) and repeating units (C) of the hydrocarbon resin polymer is 13 mol% or more, based on 100 mol% of the hydrocarbon resin polymer. The repeating units (A) and repeating units (C) affect the thermal properties and thermal stability of the hydrocarbon resin polymer. The total content of repeating units (A) and repeating units (C) of the hydrocarbon resin polymer is 13 mol% or more, which allows the hydrocarbon resin polymer to achieve excellent thermal properties and thermal stability. In some embodiments, the total content of repeating units (A) and repeating units (C) of the hydrocarbon resin polymer may be 15 mol%, 17 mol%, or 20 mol% or more, based on 100 mol% of the hydrocarbon resin polymer. In some embodiments, the total content of repeating units (A) and repeating units (C) of the hydrocarbon resin polymer may be 45 mol%, 40 mol%, or 35 mol% or less, based on 100 mol% of the hydrocarbon resin polymer.
[0042] In some embodiments, the hydrocarbon resin polymer may include reactive double bonds. In this disclosure, "reactive double bonds" refers to double bonds in repeating units (A) or repeating units (C) that can react with other compounds or polymers. For example, in some embodiments, reactive double bonds include the double bonds in repeating units (A) shown below:
[0043] [ka]
[0044] For example, in some embodiments, the reactive double bond includes a double bond on a non-benzene ring in repeat unit (C) shown below, although the disclosure is not limited thereto.
[0045] [ka]
[0046] In some embodiments, the hydrogen content of the reactive double bonds in the hydrocarbon resin polymer may be less than 10%. If the hydrogen content of the reactive double bonds in the hydrocarbon resin polymer is too high, for example, higher than 10%, the hydrocarbon resin polymer is prone to oxidation during the heating process, resulting in a decrease in the electrical performance of the hydrocarbon resin polymer. In some embodiments, the hydrogen content of the reactive double bonds in the hydrocarbon resin polymer may be greater than 0.2%. If the hydrogen content of the reactive double bonds in the hydrocarbon resin polymer is too low, for example, less than 0.2%, the peel strength of the layer containing the hydrocarbon resin polymer may be excessively low. In some embodiments, the hydrogen content of the reactive double bonds in the hydrocarbon resin polymer may be 0.2% to 10%, 0.3% to 9%, 0.4% to 8%, or 0.5% to 7%. If the hydrogen content of the reactive double bonds in the hydrocarbon resin polymer is within the above range, the hydrocarbon resin polymer is less likely to oxidize in a high temperature environment (for example, 150° C. or higher), or the crosslinking reaction tends to be completed before oxidation. Thus, the electrical performance of the hydrocarbon resin polymer may be improved. In some embodiments, the number average molecular weight (Mn) of the hydrocarbon resin polymer may be 2500 to 15000 g / mol. If the number average molecular weight of the hydrocarbon resin polymer is too high, the solubility of the hydrocarbon resin polymer may be reduced. In some embodiments, the number average molecular weight of the hydrocarbon resin polymer may be 2500 to 13000 g / mol, 2800 to 12000 g / mol, or 3000 to 11000 g / mol.
[0047] In some embodiments, the hydrocarbon resin polymer may have a polymer dispersity index (PDI) of less than 20. A polymer dispersity index of less than 20 for the hydrocarbon resin polymer provides better processability for the hydrocarbon resin polymer. In some embodiments, the polymer dispersity index for the hydrocarbon resin polymer may be greater than 1.5. In some embodiments, the polymer dispersity index for the hydrocarbon resin polymer may be from 1.5 to 20, from 2 to 18, or from 2.2 to 16.5.
[0048] In some embodiments, the resin composition may further include 5 to 350 parts by weight of a solvent. The resin composition having the above-mentioned content of the solvent may have good processability. In some embodiments, the resin composition of the present disclosure may include 6 to 340 parts by weight, 10 to 340 parts by weight, or 30 to 340 parts by weight of the solvent per 100 parts by weight of the hydrocarbon resin polymer. The solvent may be any usable organic solvent. In some embodiments, the solvent may be toluene.
[0049] In some embodiments, the resin composition may further include a monovinyl aromatic compound. In some embodiments, the resin composition of the present disclosure may include 0.1 to 50 parts by weight, 0.1 to 40 parts by weight, or 0.1 to 30 parts by weight of the monovinyl aromatic compound per 100 parts by weight of the hydrocarbon resin polymer. In some embodiments, the monovinyl aromatic compound may include styrene and / or ethylstyrene, although the present disclosure is not limited thereto.
[0050] The resin composition of the present disclosure having the above-mentioned components and contents may have at least one of the following advantages: low composition viscosity, low resin flow, low crosslinking temperature, short crosslinking time, high glass transition temperature, good electrical performance, and no smoke generation during the crosslinking process.
[0051] Some embodiments of the present disclosure provide a method for producing a resin composition. Figure 1 is a flow chart of a method for producing a resin composition according to some embodiments of the present disclosure. Referring to Figure 1, the method for producing a resin composition of the present disclosure includes the steps of preparing a mixture S101, polymerizing the mixture to form a crude composition S103, purifying the crude composition S105, and adding a divinyl aromatic compound S107.
[0052] The mixture prepared in step S101 includes an optional bridged ring compound, a monovinyl aromatic compound, and a divinylaromatic compound. In some embodiments, the mixture prepared in step S101 includes 0 to 50 mol% of the bridged ring compound, 60 to 95 mol% of the monovinyl aromatic compound, and 0.5 to 15 mol% of the divinylaromatic compound, based on 100 mol% of the mixture. In some embodiments, the mixture prepared in step S101 includes 0 to 30 mol% of the bridged ring compound, 65 to 95 mol% of the monovinyl aromatic compound, and 0.5 to 12 mol% of the divinylaromatic compound, based on 100 mol% of the mixture. In some embodiments, the mixture prepared in step S101 includes 0 to 25 mol% of the bridged ring compound, 70 to 95 mol% of the monovinyl aromatic compound, and 0.5 to 10 mol% of the divinylaromatic compound, based on 100 mol% of the mixture. Definitions and examples of bridged ring compounds, monovinyl aromatic compounds, and divinyl aromatic compounds have been described above and will not be repeated here.
[0053] In some embodiments, step S103 may include polymerizing the mixture provided in step S101 at a polymerization temperature between 0° C. and 80° C. In some embodiments, the polymerization temperature may be between 0° C. and 45° C., between 0° C. and 40° C., between 0° C. and 35° C., or between 0° C. and 30° C. In some embodiments, step S103 may include polymerizing the mixture provided in step S101 using a catalyst. In some embodiments, the catalyst may include boron trifluoride diethyl etherate (BF3-OEt2), titanium(IV) chloride (titanium tetrachloride, TiCl4), or a combination thereof, although the disclosure is not limited thereto.
[0054] The crude composition obtained in step S103 is purified in step S105. In some embodiments, step S105 may include extracting the crude composition obtained in step S103 with isopropyl alcohol (IPA), but the disclosure is not limited thereto. In some embodiments, step S105 may include extracting the crude composition obtained in step S103 with water. Step S105 may be followed by an optional step S107 of adding a divinylaromatic compound. Specifically, if the content of the divinylaromatic compound in the crude product purified in step S105 is less than 0.01 parts by weight per 100 parts by weight of the hydrocarbon resin polymer, or if it is desired to adjust the content of the divinylaromatic compound in the crude product, step S107 is further carried out. In other cases, step S107 may be omitted. For example, in some embodiments, if step S105 includes extracting the crude product with water, step S107 may be omitted. In an embodiment in which step S105 includes extracting the crude composition with isopropyl alcohol, step S107 can be performed after step S105, but the present disclosure is not limited thereto. The resin composition of the present disclosure can be obtained after step S105 or step S107.
[0055] The resin composition obtained by the method for producing the resin composition of the present disclosure has been described above, so it will not be repeated here. The method for producing the resin composition of the present disclosure can obtain the resin composition in a low-cost, low-energy, and / or environmentally friendly manner. The resin composition may have at least one of the following advantages: suitable composition viscosity, low resin flow, low crosslinking temperature, short crosslinking time, high glass transition temperature, good electrical performance, and no smoke generation during the crosslinking process.
[0056] In some embodiments, the present disclosure provides a substrate structure. Figure 2 is a schematic diagram of a substrate structure according to some embodiments of the present disclosure. Referring to Figure 2, the substrate structure of the present disclosure includes a base layer 200, a conductive layer 203 disposed on the base layer 200, and a resin layer 201 disposed between the conductive layer 203 and the base layer 200. The resin layer 201 is formed from a resin composition by the crosslinking process described above.
[0057] In some embodiments, the base layer 200 may include polyimide (PI), polycarbonate (PC), polyethylene terephthalate (PET), glass, quartz, sapphire, ceramic, plastic, Ajinomoto build-up film (ABF), fiberglass paper, cotton paper, or combinations thereof, although the present disclosure is not limited thereto.
[0058] In some embodiments, the conductive layer 203 may include copper (Cu), aluminum (Al), molybdenum (Mo), tungsten (W), gold (Au), chromium (Cr), nickel (Ni), platinum (Pt), titanium (Ti), another suitable metallic material, or a combination thereof, but the disclosure is not limited thereto. In some embodiments, the conductive layer 203 may have a single layer structure or a multi-layer stack structure. For example, the conductive layer 203 may include a single layer of metallic copper.
[0059] The base layer 200 may include a first surface 200S1 and a second surface 200S2 opposite to the first surface 200S1. The conductive layer 203 may be disposed on the first surface 200S1 of the base layer 200, and the resin layer 201 may be disposed between the first surface 200S1 of the base layer 200 and the conductive layer 203.
[0060] In some embodiments, the substrate structure may further include another conductive layer 204 on the second surface 200S2 of the base layer 200, and another resin layer 202 disposed between the second surface 200S2 of the base layer 200 and the conductive layer 204. The another resin layer 202 may include the same material as the resin layer 201. The another conductive layer 204 may include copper (Cu), aluminum (Al), molybdenum (Mo), tungsten (W), gold (Au), chromium (Cr), nickel (Ni), platinum (Pt), titanium (Ti), another suitable metal material, or a combination thereof, but the present disclosure is not limited thereto. In some embodiments, the another conductive layer 204 may have a single layer structure or a multi-layer stack structure. The another conductive layer 204 may include the same or different material and the same or different structure as the conductive layer 203. For example, the another conductive layer 204 may include a single layer of metallic copper.
[0061] The substrate structure having the above structure can be obtained in a low-cost, low-energy consumption and / or environmentally friendly manner.In addition, the substrate structure having the above structure can have at least one of the following advantages: good thermal performance (e.g., high glass transition temperature (Tg)) and good electrical performance.
[0062] One or more embodiments of the present disclosure will be described in more detail in the following examples, however, these examples are used to illustrate the embodiments of the present disclosure and are not intended to limit the scope of the embodiments of the present disclosure.
[0063] Preparation of polymers 1 to 15
[0064] Polymer 1
[0065] Reaction process 203.1 g (20 mol%) of dicyclopentadiene (DCPD), 536 g (67 mol%) of styrene, 130 g (13 mol%) of divinylbenzene (DVB; purity 63%; remaining 37% is ethylstyrene), and 1113.6 g of toluene were added under nitrogen to a 3-liter, four-neck vertical jacketed reactor with a double-layer four-wing flat blade. The mixture was stirred at 400 rpm using a stirring blade. At a low temperature (0°C), 21.8 g of boron trifluoride diethyl ether complex (BF3-OEt2) catalyst was injected at a rate of 1.0 mL / min using a syringe pump. After the catalyst was added, the reaction temperature was raised to 10°C and maintained for 10 minutes, then raised to 15°C and maintained for 3 hours. The polymerization reaction was stopped by adding 65.4 g of isopropyl alcohol to obtain a polymer stock solution. The viscosity of the polymer stock solution at the time of stopping was confirmed to be 4.7 cp.
[0066] Refining Process First, the polymer stock solution was filtered to remove impurities and insolubles. The polymer stock solution was stirred with a mechanical stirrer at a rotation speed of 500 rpm. The polymer stock solution was slowly dropped into isopropyl alcohol through an addition funnel to obtain a white resin crude product. The weight of isopropyl alcohol was 5 times that of the polymer stock solution. The solid-liquid phase was suction filtered to obtain a white solid, which was then repeatedly redissolved in toluene (weight ratio of stock solution to isopropyl alcohol was 1:5). After filtration, a white resin solid with higher purity was obtained. The white resin solid was washed with methanol to remove impurities and isopropyl alcohol, and heated and stirred under vacuum to remove the solvent to obtain a white powder of hydrocarbon resin polymer as polymer 1.
[0067] Polymer 2
[0068] Reaction process 0.6498 kg (20 mol%) dicyclopentadiene, 1.715 kg (67 mol%) styrene, 0.416 kg (13 mol%) divinylbenzene (63% purity, remaining 37% is ethyl styrene), and 3.5635 kg toluene were added to a 10 L 4-neck vertical jacketed reactor under nitrogen and stirred with a triple-layer six-wing flat blade at a stirring speed set at 200 rpm to produce a mixture. At low temperature (0°C), 0.06976 kg boron trifluoride diethyl ether complex catalyst was injected at a rate of 0.25 mL / min using a syringe pump. After catalyst addition, the reaction temperature was raised to 10°C and maintained for 10 minutes, then raised to 20°C and maintained for 2 hours. 0.2092 kg isopropyl alcohol was added to terminate the polymerization reaction, yielding a polymer stock solution. The viscosity of the polymer stock solution at the time of termination was determined to be 11.67 cp.
[0069] Refining Process A bag filter was used to filter impurities and insolubles in the polymer stock solution. An air pump was used to inject isopropyl alcohol into another large mixing tank equipped with a mechanical stirrer at a rotation speed of 300 rpm. The weight of isopropyl alcohol was 5 times that of the polymer stock solution. A hose pump (rotation speed set at 100 rpm) was used to slowly inject the polymer stock solution, precipitating a white resin crude product in the tank. The solid-liquid phase was filtered through a large filter press to obtain a white solid, which was then repeatedly redissolved in toluene (weight ratio of polymer stock solution to isopropyl alcohol was 1:5). After filtration, a white resin solid with higher purity was obtained. The white resin solid was washed with methanol to remove impurities and isopropyl alcohol, and heated and stirred under vacuum to remove the solvent, obtaining a white powder of hydrocarbon resin polymer as polymer 2.
[0070] Polymer 3
[0071] Reaction process 21.6 g (17 mol%) of dicyclopentadiene (95% purity), 70 g (70 mol%) of styrene (99.8% purity), 16.25 g (13 mol%) of divinylbenzene (63% purity, remaining 37% is ethyl styrene), and 160 mL of toluene were added to a 1-liter 4-neck vertical jacketed reactor under nitrogen and stirred with a single-layer four-wing flat blade at a stirring speed set at 400 rpm to produce a mixture. At low temperature (10°C), 2.73 g of boron trifluoride diethyl ether complex catalyst was injected at a rate of 0.25 mL / min using a syringe pump. After adding the catalyst, the reaction was allowed to proceed for 2 hours. The polymerization reaction was quenched by adding 8.1 g of isopropyl alcohol to obtain a polymer stock solution.
[0072] Refining Process First, the polymer stock solution was filtered to remove impurities and insolubles. The polymer stock solution was stirred with a mechanical stirrer at a rotation speed of 500 rpm. The polymer stock solution was slowly dropped into isopropyl alcohol through an addition funnel to obtain a white resin crude product. The weight of isopropyl alcohol was 5 times that of the polymer stock solution. The solid-liquid phase was suction filtered to obtain a white solid, which was then repeatedly redissolved in toluene (the weight ratio of the polymer stock solution to isopropyl alcohol was 1:5). After filtration, a white resin solid with higher purity was obtained. The white resin solid was washed with methanol to remove impurities and isopropyl alcohol, and heated and stirred under vacuum to remove the solvent to obtain a white powder of hydrocarbon resin polymer as polymer 3.
[0073] Polymer 4
[0074] Reaction process 69.70 g (87 mol%) of styrene, 13.02 g (13 mol%) of divinylbenzene (63% purity, the remaining 37% being ethylstyrene), and 222.31 g of toluene were added to a 1-liter 4-neck vertical jacketed reactor under nitrogen and stirred with a four-wing flat blade at a stirring speed set at 400 rpm to produce a mixture. 1.1 g of boron trifluoride diethyl ether complex catalyst was injected using a syringe pump at a rate of 0.25 mL / min at a reaction temperature of 20°C. After 1.5 hours, 69 g of water was added to quench the polymerization reaction, yielding a polymer stock solution.
[0075] Refining Process First, the polymer stock solution was filtered to remove impurities and insolubles. The polymer stock solution was stirred with a mechanical stirrer at a rotation speed of 500 rpm. The polymer stock solution was slowly dripped into isopropyl alcohol through an addition funnel to obtain a white resin crude product. The weight of isopropyl alcohol was 5 times the weight of the polymer stock solution. The solid-liquid phase was suction filtered to obtain a white solid. The white resin solid was washed with methanol to remove impurities and isopropyl alcohol, and heated to 60°C under nitrogen to remove the solvent, obtaining a white powder of hydrocarbon resin polymer as polymer 4. The yield was about 50%.
[0076] Polymer 5
[0077] Reaction process 34.88 g (87 mol%) of styrene, 6.51 g (13 mol%) of divinylbenzene (63% purity, the remaining 37% being ethylstyrene), and 222.63 g of toluene were added to a 1-L 4-neck vertical jacketed reactor under nitrogen and stirred with a 4-blade flat blade at a stirring speed set at 400 rpm to produce a mixture. 1.1 g of boron trifluoride diethyl ether complex catalyst was injected using a syringe pump at a rate of 0.25 mL / min at a reaction temperature of 20 °C. After 4 hours, 3.96 g of isopropyl alcohol was added to quench the polymerization reaction, yielding a polymer stock solution.
[0078] Refining Process First, the polymer stock solution was diluted with 94 g of toluene. The polymer stock solution was stirred with a mechanical stirrer at a rotation speed of 500 rpm. The polymer stock solution was slowly dripped into isopropyl alcohol through an addition funnel to obtain a white resin crude product. The weight of isopropyl alcohol was 5 times the weight of the polymer stock solution. The solid-liquid phase was suction filtered to obtain a white solid. The white solid was washed with methanol to remove impurities and isopropyl alcohol, and heated to 60° C. under nitrogen to remove the solvent, obtaining a white powder of hydrocarbon resin polymer as polymer 5. The yield was about 50%.
[0079] Polymer 6
[0080] Reaction process 3.59 g (5.7 mol%) of divinylbenzene (63% purity, remaining 37% is ethyl styrene) and 19.2 g (87 mol%) of styrene were added to a 250 mL round bottom flask under nitrogen. 20 g of xylene mixture was added to the above mixture at 25 °C. 0.1 mL of 1 M TiCl4 solution and 0.006 g of NaBArF4 were added to initiate the polymerization reaction. After 30 min, the color of the mixture changed from colorless to red. 1 mL of isopropyl alcohol was added to quench the polymerization reaction, obtaining a polymer solution.
[0081] Refining Process The polymer solution was precipitated from isopropyl alcohol (IPA, 500 mL) to obtain an orange powder, which was dried at 60° C. for 3 hours to obtain Polymer 6. The yield was 18.6 g (81%).
[0082] Polymer 7
[0083] Reaction process 21.58 g (17 mol%) of dicyclopentadiene (95% purity), 52.99 g (53 mol%) of styrene (99.8% purity), 37.50 g (30 mol%) of divinylbenzene (63% purity, remaining 37% is ethyl styrene), and 160 mL of toluene were added to a 1-L 4-neck vertical jacketed reactor under nitrogen and stirred with a single-layer 4-blade flat blade at a stirring speed set at 400 rpm to produce a mixture. At low temperature (0 °C), 1.36 g of boron trifluoride diethyl ether complex catalyst was injected at a rate of 0.25 mL / min using a syringe pump. After adding the catalyst, the reaction was allowed to proceed for 2 hours. The polymerization reaction was quenched by adding 4.1 g of isopropyl alcohol to obtain a colorless polymer stock solution.
[0084] Refining Process First, the polymer stock solution was filtered to remove impurities and insolubles. The polymer stock solution was stirred with a mechanical stirrer at a rotation speed of 500 rpm. The polymer stock solution was slowly dropped into isopropyl alcohol through an addition funnel to obtain a white resin crude product. The weight of isopropyl alcohol was 5 times that of the polymer stock solution. The solid-liquid phase was suction filtered to obtain a white solid, which was then repeatedly redissolved in toluene (the weight ratio of the polymer stock solution to isopropyl alcohol was 1:5). After filtration, a white resin solid with higher purity was obtained. The white resin solid was heated and stirred under vacuum to remove the solvent, and 30.5 g of a white powder of a hydrocarbon resin polymer was obtained as polymer 7.
[0085] Polymer 8
[0086] Reaction process 21.58 g (17 mol%) of dicyclopentadiene (95% purity), 56.99 g (57 mol%) of styrene (99.8% purity), 32.50 g (26 mol%) of divinylbenzene (63% purity, remaining 37% is ethyl styrene), and 160 mL of toluene were added to a 1-L 4-neck vertical jacketed reactor under nitrogen and stirred with a single-layer 4-blade flat blade at a stirring speed set at 400 rpm to produce a mixture. At low temperature (0 °C), 1.36 g of boron trifluoride diethyl ether complex catalyst was injected at a rate of 0.25 mL / min using a syringe pump. After adding the catalyst, the reaction was allowed to proceed for 2 hours. The polymerization reaction was quenched by adding 4.1 g of isopropyl alcohol to obtain a colorless polymer stock solution.
[0087] Refining Process First, the polymer stock solution was filtered to remove impurities and insolubles. The polymer stock solution was stirred with a mechanical stirrer at a rotation speed of 500 rpm. The polymer stock solution was slowly dropped into isopropyl alcohol through an addition funnel to obtain a white resin crude product. The weight of isopropyl alcohol was 5 times that of the polymer stock solution. The solid-liquid phase was suction filtered to obtain a white solid, which was then repeatedly redissolved in toluene (the weight ratio of the polymer stock solution to isopropyl alcohol was 1:5). After filtration, a white resin solid with higher purity was obtained. The white resin solid was washed with methanol to remove impurities and isopropyl alcohol, and heated and stirred under vacuum to remove the solvent to obtain 35.7 g of a white powder of hydrocarbon resin polymer as polymer 8.
[0088] Polymer 9
[0089] Reaction process 21.6 g (17 mol%) of dicyclopentadiene (95% purity), 59.99 g (60 mol%) of styrene (99.8% purity), 28.75 g (23 mol%) of divinylbenzene (63% purity, remaining 37% is ethyl styrene), and 160 mL of toluene were added to a 1-L 4-neck vertical jacketed reactor under nitrogen and stirred with a single-layer 4-blade flat blade at a stirring speed set at 400 rpm to produce a mixture. At low temperature (0 °C), 2.73 g of boron trifluoride diethyl ether complex catalyst was injected at a rate of 0.25 mL / min using a syringe pump. After adding the catalyst, the reaction was allowed to proceed for 2 hours. The polymerization reaction was quenched by adding 8.1 g of isopropyl alcohol to obtain a colorless polymer stock solution.
[0090] Refining Process First, the polymer stock solution was filtered to remove impurities and insolubles. The polymer stock solution was stirred with a mechanical stirrer at a rotation speed of 500 rpm. The polymer stock solution was slowly dropped into isopropyl alcohol through an addition funnel to obtain a white resin crude product. The weight of isopropyl alcohol was 5 times that of the polymer stock solution. The solid-liquid phase was suction filtered to obtain a white solid, which was then repeatedly redissolved in toluene (the weight ratio of the polymer stock solution to isopropyl alcohol was 1:5). After filtration, a white resin solid with higher purity was obtained. The white resin solid was washed with methanol to remove impurities and isopropyl alcohol, and heated and stirred under vacuum to remove the solvent to obtain 40.1 g of a white powder of hydrocarbon resin polymer as polymer 9.
[0091] Polymer 10
[0092] Reaction process 24.9 g (30 mol%) of divinylbenzene (63% purity, remaining 37% is ethyl styrene) and 46.5 g (70 mol%) of styrene were added to a 250 mL round bottom flask under nitrogen. 60 g of toluene was added to the above mixture at 40°C. 2.6 g of 1 M TiCl4 solution was added to initiate the polymerization reaction. After 3 hours, the color of the mixture changed from colorless to red / brown. 1 mL of isopropyl alcohol was added to quench the polymerization reaction, obtaining a polymer solution.
[0093] Refining Process The red polymer solution was precipitated from isopropyl alcohol (IPA, 500 mL) to give an orange powder, which was dried at 60° C. for 3 h to give polymer 10. The yield was 37.8 g (53%).
[0094] Polymer 11
[0095] Reaction process 12.7 g (40 mol%) of divinylbenzene (purity 63%, remaining 37% is ethyl styrene) and 15.3 g (60 mol%) of styrene were added to a 250 mL round bottom flask under nitrogen. 50 g of toluene was added to the above mixture at 75 °C. 0.15 g of BF3-OEt2 solution was added to initiate the polymerization reaction. After 1.5 h, the color of the mixture changed from colorless to yellow. 1 mL of isopropyl alcohol was added to quench the polymerization reaction, and a polymer solution was obtained.
[0096] Refining Process The red polymer solution was precipitated from isopropyl alcohol (IPA, 500 mL) to give an orange powder, which was dried at 60° C. for 3 h to give polymer 11. The yield was 16.0 g (57%).
[0097] Polymer 12
[0098] Reaction process 37.49 g (60 mol%) of styrene, 15.63 g (20 mol%) of divinylbenzene (63% purity, the remaining 37% being ethylstyrene), 15.864 g (20 mol%) of dicyclopentadiene (DCPD), and 173.4 g of toluene were added to a 1-liter 4-neck vertical jacketed reactor under nitrogen and stirred with a 4-blade flat blade at a stirring speed set at 400 rpm to produce a mixture. 1.7 g of boron trifluoride diethyl ether complex catalyst was injected using a syringe pump at a rate of 0.25 mL / min at a reaction temperature of 20 °C. After 3 h, 5.37 g of isopropyl alcohol was added to quench the polymerization reaction, yielding a polymer stock solution.
[0099] Refining Process First, the polymer stock solution was diluted with 62 g of toluene. The polymer stock solution was stirred with a mechanical stirrer at a rotation speed of 500 rpm. The polymer stock solution was slowly dripped into isopropyl alcohol through an addition funnel to obtain a white resin crude product. The weight of isopropyl alcohol was 5 times the weight of the polymer stock solution. The solid-liquid phase was suction filtered to obtain a white solid. The white solid was washed with methanol to remove impurities and isopropyl alcohol, and heated to 60° C. under nitrogen to remove the solvent, obtaining a white powder of hydrocarbon resin polymer as polymer 12. The yield was about 38%.
[0100] Varnish solution containing polymer 13
[0101] Reaction process Dicyclopentadiene (DCPD) 20 mol%, divinylbenzene (63% purity, the remaining 37% is ethylstyrene) 13 mol%, styrene 67 mol%, and toluene were added to a 1 L jacketed reactor at 20°C under nitrogen. Boron trifluoride diethyl etherate was added to initiate the polymerization reaction. The color of the mixture slowly changed from colorless to brown. The mixture was stirred at 20°C for 1 hour, and then water was added to quench the polymerization reaction, yielding a polymer stock solution.
[0102] Refining Process First, the polymer stock solution was filtered to remove impurities and water. The polymer stock solution was allowed to stand at room temperature for 0 to 30 minutes. The yellow layer of the polymer stock solution was collected and then concentrated using a rotary evaporator to obtain a varnish solution containing 50 wt% of a hydrocarbon resin polymer (polymer 13). After analysis, it was found that in the varnish solution containing polymer 13, for 100 parts by weight of polymer 13, the varnish solution further contained 4.77 parts by weight of divinylbenzene, 3.5 parts by weight of ethylstyrene, 16 parts by weight of styrene, and 8.5 parts by weight of toluene.
[0103] Varnish solution containing polymer 14
[0104] Reaction process Dicyclopentadiene (DCPD) 20 mol%, divinylbenzene (63% purity, the remaining 37% is ethylstyrene) 13 mol%, styrene 67 mol%, and toluene were added to a 1 L jacketed reactor at 20°C under nitrogen. Boron trifluoride diethyl etherate was added to initiate the polymerization reaction. The color of the mixture slowly changed from colorless to brown. The mixture was stirred at 20°C for 2 hours, and then water was added to quench the polymerization reaction, yielding a polymer stock solution.
[0105] Refining Process First, the polymer stock solution was filtered to remove impurities and water. The polymer stock solution was allowed to stand at room temperature for 0 to 30 minutes. The yellow layer of the polymer stock solution was collected and then concentrated using a rotary evaporator to obtain a varnish solution containing 50 wt% of a hydrocarbon resin polymer (polymer 14). After analysis, it was found that in the varnish solution containing polymer 14, for 100 parts by weight of polymer 14, the varnish solution further contained 1.9 parts by weight of divinylbenzene, 1.8 parts by weight of ethylstyrene, 12 parts by weight of styrene, and 28 parts by weight of toluene.
[0106] The materials and ratios used to prepare the varnish solutions containing polymers 1 to 12 and polymers 13 and 14 described above are shown in Table 1 below. The polymerization times, polymerization temperatures, catalysts, and yields are shown in Table 2 below.
[0107] [Table 1]
[0108] [Table 2]
[0109] Using a nuclear magnetic resonance spectrometer (NMR, JEOL, JNM-ECZ400S), 13 C-NMR and 1 The structural composition of polymers 1 to 14 was analyzed by H-NMR. It was found that polymers 1 to 14 contained repeating units (A) derived from bridged cyclic compounds, repeating units (B) derived from monovinyl aromatic compounds, and repeating units (C) derived from divinylaromatic compounds. Table 3 shows the content of repeating units (A) derived from bridged cyclic compounds, the content of repeating units (B) derived from monovinyl aromatic compounds, the content of repeating units (C) derived from divinylaromatic compounds, and the total content of repeating units (A) and repeating units (C).
[0110] [Table 3]
[0111] Measurement of physical / chemical properties of polymers 1 to 14 [Measurement of hydrogen content in reactive double bonds] Polymer 1 to polymer 14 were each dissolved in deuterated chloroform (CDCl3). The hydrogen content in the reactive double bonds of polymers 1 to 14 were each measured by NMR (JEOL, JNM-ECZ400S / L1). Specifically, the hydrogen content in the reactive double bonds of polymers 1 to 14 was calculated by dividing the sum of the integrals of the hydrogen in the reactive double bonds by the sum of the integrals of all hydrogen.
[0112] [Measurement of number average molecular weight (Mn) and polymer dispersion index (PDI)]
[0113] The number average molecular weight (Mn) and polymer dispersity index (PDI) of polymers 1 to 14 were measured by gel permeation chromatography (GPC) (Waters APC, column: Waters Acquity XT900) using polystyrene as standard.
[0114] Specifically, 5 mL of tetrahydrofuran (THF) was added to 0.01 g of polymer 1 to 14, respectively, to prepare samples of polymer 1 to 14. The samples of polymer 1 to 14 were filtered through a 0.22 μm filter and analyzed by the instrument to obtain the number average molecular weight (Mn) and polymer dispersity index (PDI) of polymer 1 to 14.
[0115] [Measurement of the content of crosslinkable repeating units (C1)] The structures of polymers 1 to 14 were analyzed by NMR (JEOL, JNM-ECZ400S / L1) and GPC (Waters). CDCl3 was used as the solvent, and the CDCl3 resonance line was used as the internal standard to obtain the content of crosslinkable repeating units (C1) in polymers 1 to 14.
[0116] The number average molecular weight (Mn), polymer dispersity index (PDI), hydrogen content in reactive double bonds, and crosslinkable repeating unit (C1) content of polymers 1 to 14 are shown in Table 4 below.
[0117] [Table 4]
[0118] According to the ratios shown in Table 5-1 below, 100 parts by weight of polymers 1 to 12 were mixed with DVB, EVB, styrene, and toluene, respectively, to prepare varnish solutions containing polymers (corresponding to the resin compositions of the present disclosure). Then, additional components were added to obtain compositions of Examples 1 to 45. Furthermore, the contents of each component in the varnish solutions containing polymer 13 and varnish solutions containing polymer 14 (corresponding to the resin compositions of the present disclosure) are shown in Table 5-2 below. According to the ratios shown in Table 5-2, additional components were added to obtain compositions of Examples 46 and 47. The contents of each component shown in Tables 5-1 and 5-2 are expressed in parts by weight. For example, in Table 5-1, Example 1 contains 100 parts by weight of polymer 1, 100 parts by weight of toluene, 15 parts by weight of toughener, 0.3 parts by weight of peroxide, and 30 parts by weight of filler. In Tables 5-1 and 5-2, the toughening agent may be a butadiene copolymer such as Ricon 100 or Ricon 257, and the resin may be a polyphenylene ether such as SA9000. The filler may be SVC available from Admatch or SS-10 available from Tokuyama. The peroxide may be Perbutyl P available from NOF Co., Ltd. In the examples containing fillers, the fillers were zirconium ground to ensure uniform dispersion in the composition.
[0119] [Table 5-1(1)]
[0120] [Table 5-1(2)]
[0121] [Table 5-2]
[0122] Characterization of substrate samples of compositions of Examples 1 to 23, 46, and 47
[0123] Glass fiber cloth (Asahi 2116, Dk / Df=3.3 / 0.0030 at 28GHz) was immersed in the compositions of Examples 1 to 23, 46, and 47, respectively. Then, the glass fiber cloth was taken out and baked at 160°C for 7 minutes to obtain the prepregs of Examples 1 to 23, 46, and 47. Two prepregs were laminated together with two copper foil layers (RTF, Hoz (18μm), Rz: 3.5μm) so that the two prepregs were located between the two copper foil layers. Silane adhesive (KBM503) was applied between the copper foil layers and the prepregs. At a temperature of 180°C to 210°C, a pressure of 441psi was applied for 3 hours to obtain the substrate samples of Examples 1 to 23, 46, and 47.
[0124] [Measurement of glass transition temperature (Tg)]
[0125] The substrate samples of Examples 1 to 23, 46, and 47 were heated from 25°C to 270°C at a rate of 3°C / min. The glass transition temperatures (Tg) of the substrate samples of Examples 1 to 23, 46, and 47 were measured by dynamic mechanical analysis (DMA, TA / Q800). The test frequency was 1Hz. The glass transition temperatures (Tg) of the substrate samples of Examples 1 to 23, 46, and 47 were obtained from the peak of tan Delta in the DMA chart.
[0126] [Thermal decomposition temperature (Td)] The thermal decomposition temperature (Td) of the substrate samples of Examples 1 to 23, 46, and 47 was measured by thermogravimetric analysis (TGA, TA / Q500). The test temperature range was from room temperature to 900° C. There was no nitrogen flow protection, and the heating rate was 10° C. / min.
[0127] [Measurement of resin flow] After forming the substrate sample, the edge of the resin layer of the substrate sample was measured using a length measuring tool (e.g., a ruler) to measure the length of resin flow. Specifically, the substrate sample included a copper foil layer and a resin layer including the composition of Examples 1 to 23, 46, and 47, and the composition of Examples 1 to 23, 46, and 47 partially overflowed (i.e., protruded from the fiberglass cloth) during the thermoforming step. The length of resin flow was determined as the average of the measured lengths of the composition of Examples 1 to 23, 46, and 47 protruding from the edge of the fiberglass cloth.
[0128] [Measurement of Percentage of Thermal Expansion (PTE)] A Thermomechanical Analysis (Model: Q400, Manufacturer: TA) was used according to the following steps:
[0129] Cycles 1 to 4 were performed in sequence. Cycle 3 was set as the measurement reference. The dimensions were taken at different temperatures (50°C and 260°C) and the percentage of size change was calculated. Cycle 1: Equilibrated at 25°C under N2 environment, kept constant temperature for 1 min, and heated from 25°C to 270°C at a rate of 20°C / min. Cycle 2: Cooled from 270°C to 25°C at a rate of 20°C / min, kept constant temperature for 1 min, and equilibrated at 25°C. Cycle 3: Heated from 25°C to 270°C at a rate of 10°C / min. Cycle 4: Cooled from 270°C to 25°C at a rate of 20°C / min.
[0130] [Electrical performance test] The Dk / Df of the substrate samples of Examples 1 to 23, 46, and 47 were measured at 10 GHz, 28 GHz, and 40 GHz using a network analyzer Keysight, P5007A, SCR.
[0131] [Peel strength test] Glass fiber cloth (Asahi 2116, Dk / Df=3.3 / 0.0030 at 28GHz) was immersed in the compositions of Examples 1 to 23, 46, and 47, respectively. Then, the glass fiber cloth was taken out and baked at 160°C for 7 minutes to obtain the prepregs of Examples 1 to 23, 46, and 47. Silane adhesive (KBM503) was applied on the surface of two copper foil layers. Four prepregs were laminated together with two copper foil layers (RTF, Hoz (18μm), Rz: 3.5μm) so that four prepregs were located between two copper foil layers. Silane adhesive (KBM503) was applied between the copper foil layers and the prepregs. At a temperature of 180°C to 210°C, a pressure of 441psi was applied for 3 hours to obtain the substrate samples of Examples 1 to 23, 46, and 47. Next, the peel strength of the substrate samples of Examples 1 to 23, 46, and 47 having a size of 12.7 mm×20 mm was measured using a SHIMADZU AG-X plus at a peel speed of 50.8 mm / min.
[0132] The resin flow, peel strength, glass transition temperature, PTE, and Td of the substrate samples of Examples 1 to 23, 46, and 47 are shown in Table 6 below. The dielectric constant / loss tangent (Dk / Df) of the substrate samples of Examples 1 to 23, 46, and 47 at 10 GHz, 28 GHz, and 40 GHz are shown in Table 7 below.
[0133] [Table 6]
[0134] [Table 7]
[0135] [Measurement of rheological properties] Using a pipette, 0.55 mL of the compositions of Examples 24 to 45 was drawn and placed on a rheometer (Model: MCR302, Manufacturer: Anton Paar). A temperature scan was performed to measure the change in the rheological properties of the compositions of Examples 24 to 45 in the temperature range of 40° C. to 210° C. with the following parameters: pre-equilibration: shear rate=1 (1 / s) held for 60 seconds, hold time: 60 seconds (40° C.), experimental temperature: 40 to 210° C., strain: 0.1%, and frequency: 10 rad / s.
[0136] The rheological properties measured include loss modulus and storage modulus. Loss modulus is often associated with fluid properties. Thus, it can be said that the loss modulus reflects the behavior of the material in the liquid state. Storage modulus is often associated with solid properties. Thus, it can be said that the storage modulus reflects the behavior of the material in the solid state. The change in loss modulus and storage modulus as the temperature is increased can be used to understand the process by which the resin composition changes from a liquid to a solid state.
[0137] FIG. 3 is a graph showing the relationship between the storage modulus and the loss modulus of the composition of Example 30 and temperature. It can be seen from FIG. 3 that the loss modulus can be higher at low temperatures, which indicates that the composition of Example 30 exhibits more liquid-state properties at low temperatures. At 146.89°C, the storage modulus begins to exceed the loss modulus, indicating that the composition of Example 30 is gradually transitioning to a solid state, which is because the composition of Example 30 begins to crosslink or harden. At higher temperatures, the storage modulus of the composition of Example 30 is significantly higher than the loss modulus, indicating that the material is behaving primarily in a solid state. The temperature at which the storage modulus of each composition begins to exceed the loss modulus is defined herein as the crosslinkable temperature. In other words, according to FIG. 3, the crosslinkable temperature of the composition of Example 30 is approximately 146.89°C.
[0138] [Measurement of storage modulus at 2000 seconds] Using a pipette, 0.55 mL of the compositions of Examples 24 to 45 was drawn and placed on a rheometer (Model: MCR302, Manufacturer: Anton Paar). Time scans were performed with the following parameters: pre-equilibration: shear rate = 1 (1 / s) for 60 seconds, experimental temperature: 160°C, strain: 0.1%, and frequency: 10 rad / s. The storage modulus of the compositions of Examples 24 to 45 at 2000 seconds was measured.
[0139] FIG. 4 is a graph showing the relationship between the storage modulus and the loss modulus of the composition of Example 30 and time. Referring to FIG. 4, it can be seen that at a crosslinking temperature of 160° C., the storage modulus of the composition of Example 30 increases with increasing crosslinking time. After 2000 seconds of crosslinking time, the increase in the storage modulus levels off. Referring to FIG. 4, it can be seen that at a crosslinking temperature of 160° C. and after 2000 seconds of crosslinking time, the storage modulus of the composition of Example 30 is 529520 Pa.
[0140] [Measurement of required crosslinking time] As described above, the crosslinking time corresponding to the storage modulus obtained by multiplying the storage modulus after 2000 seconds of crosslinking time of the compositions of Examples 24 to 45 by 0.9 during time scanning is defined as the "required crosslinking time." Specifically, referring to FIG. 4, it can be seen that the storage modulus of the composition of Example 30 is 529520 Pa after a crosslinking temperature of 160° C. and a crosslinking time of 2000 seconds. The "required crosslinking time" is 1490 seconds (the crosslinking time corresponding to obtaining a storage modulus of 476568 Pa (0.9×529520)).
[0141] [Measurement of complex viscosity of composition at 1 / 2 the required crosslinking time] As described above, the complex viscosities of the compositions of Examples 24 to 45 were measured after half the "required crosslinking time" during the time scan and recorded as "complex viscosity at 1 / 2 the required crosslinking time." FIG. 5 is a graph showing the complex viscosity versus time for the composition of Example 30. Referring to FIG. 5, at a crosslinking temperature of 160° C., after half the "required crosslinking time" (i.e., 1490 s / 2=745 s), the complex viscosity of the composition of Example 30 was 3.82×10 7 cP.
[0142] The measured crosslinkable temperatures, required crosslinking times, complex viscosities at 1 / 2 the required crosslinking times, and storage moduli at 2000 seconds for the compositions of Examples 24 to 45 are shown in Table 8 below.
[0143] [Table 8]
[0144] FIG. 6 is a graph showing the relationship between the glass transition temperature of the resin composition according to the present disclosure and the DVB content in the resin composition. FIG. 6(a) is a graph showing the relationship between the glass transition temperature of the substrate samples of Examples 1 to 4 and the DVB content in the compositions of Examples 1 to 4. FIG. 6(b) is a graph showing the relationship between the glass transition temperature of the substrate samples of Examples 5 to 11 and the DVB content in the compositions of Examples 5 to 11. FIG. 6(c) is a graph showing the relationship between the glass transition temperature of the substrate samples of Examples 12 to 15 and the DVB content in the compositions of Examples 12 to 15. From FIG. 6, it can be seen that the glass transition temperature increases as the DVB content in the resin composition increases. Specifically, from FIG. 6(a), it can be seen that the substrate samples of Examples 2 to 4 have higher glass transition temperatures than the substrate sample of Example 1 (not containing DVB). 6(b) shows that the substrate samples of Examples 7 to 11 have higher glass transition temperatures than the substrate sample of Example 5 (not containing DVB), and the glass transition temperatures are proportional to the DVB content in the composition. FIG. 6(c) shows that the substrate samples of Examples 13 to 15 have higher glass transition temperatures than the substrate sample of Example 12 (not containing DVB), and the glass transition temperatures are proportional to the DVB content in the composition.
[0145] FIG. 7 is a graph showing the relationship between the resin flow of the resin composition according to the present disclosure and the DVB content in the resin composition. FIG. 7(a) is a graph showing the relationship between the resin flow of the substrate samples of Examples 1 to 4 and the DVB content in the compositions of Examples 1 to 4. FIG. 7(b) is a graph showing the relationship between the resin flow of the substrate samples of Examples 5 to 11 and the DVB content in the compositions of Examples 5 to 11. FIG. 7(c) is a graph showing the relationship between the resin flow of the substrate samples of Examples 12 to 15 and the DVB content in the compositions of Examples 12 to 15. From FIG. 7(a), it can be seen that the resin flow of the substrate samples of Examples 2 to 4 is improved compared to the substrate sample of Example 1 (not containing DVB), and the length of the resin flow is inversely proportional to the DVB content in the composition. From FIG. 7(b), it can be seen that the resin flow of the substrate samples of Examples 7 to 11 is improved compared to the substrate sample of Example 5 (not containing DVB), and the length of the resin flow is inversely proportional to the DVB content in the composition. FIG. 7(c) shows that the resin flow of the substrate sample of Example 15 is improved compared to the substrate sample of Example 12 (which does not contain DVB).
[0146] From Table 7, it can be seen that the composition of the present disclosure has excellent electrical performance. Specifically, compared with the substrate samples of Examples 16 to 18 (containing TAIC but not containing DVB), the loss tangent (Df) of the substrate samples of Examples 13 to 15 (containing DVB but not containing TAIC) at 10 GHz, 28 GHz, and 40 GHz is lower (i.e., improved). FIG. 8 is a graph showing the relationship between the loss tangent (Df) of the substrate samples of Examples 13 to 15 and the DVB / TAIC content in the resin composition. From FIG. 8, it can be seen that the same content of DVB has better electrical performance (lower Df) than TAIC. In other words, according to Table 7 and FIG. 8, when the composition of the present disclosure is used to subsequently prepare prepregs and copper foil substrates, substrate samples with excellent electrical properties can be completed without using a conventional crosslinking agent, such as triallylisocyanurate (TAIC).
[0147] In addition, there is no need to use TAIC crosslinker when preparing prepregs and copper foil substrates using the composition of the present disclosure, so no smoke is generated.Compared with TAIC crosslinker, DVB in the composition can also increase the solubility of hydrocarbon resin polymers, resulting in improved processability.
[0148] According to Table 8, when the same polymer is contained, Examples 28, 30, 32, 34, and 40 containing more than 0.01 parts by weight of DVB have a lower crosslinkable temperature and / or a shorter crosslinking time than Examples 29, 31, 33, 35, and 41 not containing DVB. Therefore, when the same polymer is contained, when the DVB is 0.01 to 50 parts by weight, the crosslinking reaction can be carried out in a shorter time and / or at a lower temperature, and the energy consumption required for the crosslinking reaction is reduced.
[0149] 100 parts by weight of polymer 1 and 100 parts by weight of toluene were mixed to prepare composition A. 10 parts by weight of DVB, 100 parts by weight of polymer 1, and 100 parts by weight of toluene were mixed to prepare composition B. 20 parts by weight of DVB, 100 parts by weight of polymer 1, and 100 parts by weight of toluene were mixed to prepare composition C. The viscosities of compositions A to C were measured at 25° C. using a TOKI SANGYO electromagnetic force balance viscometer. The measured viscosities are shown in Table 9 below. The content of each component in Table 9 is shown in parts by weight.
[0150] [Table 9]
[0151] From Table 9, it can be seen that DVB in the composition can reduce the viscosity of the resin composition, resulting in better processability. Specifically, the viscosity of compositions B and C (containing DVB) is significantly reduced compared to composition A (not containing DVB).
[0152] According to the above examples and test results, in some examples, the resin composition of the present disclosure is produced without the need for organic solvents for purification, which is environmentally friendly and reduces costs. The resin composition of the present disclosure has low composition viscosity, low crosslinking temperature, and short crosslinking time, so that the use of the resin composition of the present disclosure to produce a substrate structure may have the advantages of low energy consumption, low cost, and / or environmental friendliness. In addition, the use of the resin composition of the present disclosure to produce a substrate structure does not produce smoke and improves resin flow. The substrate structure produced from the resin composition of the present disclosure also has good thermal properties (high glass transition temperature (Tg)) and / or electrical performance.
[0153] While the present invention has been described by way of example and in terms of a preferred embodiment, it is to be understood that the invention is not limited to the disclosed embodiment. On the contrary, it is intended to cover various modifications and similar arrangements (as would be apparent to those skilled in the art). Thus, the scope of the appended claims should be accorded the broadest interpretation so as to encompass all such modifications and similar arrangements. [Explanation of symbols]
[0154] S101, S103, S105, S107…Step 200…Base layer 200S1…First surface 200S2…Second surface 201, 202: resin layer 203, 204: conductive layer
Claims
1. 100 parts by weight of a hydrocarbon resin polymer; 0.01 to 50 parts by weight of a divinylaromatic compound; A resin composition comprising:
2. The hydrocarbon resin polymer is, relative to 100 mol % of the hydrocarbon resin polymer, 15 to 95 mol % of a repeating unit (B) derived from a monovinyl aromatic compound; 5 to 85 mol % of repeating units (C) derived from a divinyl aromatic compound; The resin composition according to claim 1 .
3. The resin composition according to claim 2 , wherein the hydrocarbon resin polymer further comprises 0.15 to 15 mol % of a repeating unit (A) derived from a bridged ring compound, based on 100 mol % of the hydrocarbon resin polymer.
4. The resin composition according to claim 3 , wherein the total amount of the repeating unit (A) and the repeating unit (C) of the hydrocarbon resin is 13 mol % or more relative to 100 mol % of the hydrocarbon resin polymer.
5. 4. The resin composition of claim 3, wherein the hydrogen atom content in reactive double bonds of the hydrocarbon resin polymer is less than 10%.
6. The repeating unit (C) comprises a crosslinkable repeating unit (C1) and a crosslinking repeating unit (C2), 【Chemistry 1】 (wherein R1, R2, R3, and R4 are each independently H or C 1-20 Ar1 and Ar2 are alkyl groups, and Ar1 and Ar2 are phenylene groups. * indicates the position where the crosslinkable repeating unit (C1) and the crosslinking repeating unit (C2) are linked to other groups or units. The resin composition according to claim 2, wherein the content of the crosslinkable repeating unit (C1) is 1 to 30 mol % based on 100 mol % of the hydrocarbon resin polymer.
7. The resin composition according to claim 1, wherein the crosslinkable temperature of the resin composition is from 125°C to 165°C.
8. The resin composition according to claim 1, wherein the resin composition has a storage modulus of 10,000 to 10,000,000 Pa after a crosslinking temperature of 160° C. and a crosslinking time of 2,000 seconds.
9. The resin composition according to claim 8, wherein the crosslinking time required for the resin composition to reach 0.9 times the storage modulus is from 1300 to 1900 seconds.
10. At a crosslinking temperature of 160° C., after half the required crosslinking time has elapsed, the complex viscosity of the resin composition is 1.00×10 4 From 6.00 x 10 8 The resin composition according to claim 9, wherein the resin composition is a tertiary phosphate.
11. A method for producing a resin composition, comprising: providing a mixture, said mixture comprising a monovinylaromatic compound and a divinylaromatic compound, and optionally a bridged ring compound; polymerizing the mixture to form a crude composition; purifying the crude composition to produce a resin composition; The resin composition comprises: 100 parts by weight of a hydrocarbon resin polymer; 0.01 to 50 parts by weight of a divinylaromatic compound; A method for producing a resin composition comprising the steps of:
12. The method of claim 11, wherein the step of purifying the crude composition comprises extracting the crude composition with water.
13. 12. The method for producing the resin composition according to claim 11, wherein the method further comprises adding a divinyl aromatic compound after the step of purifying the crude composition, and the step of purifying the crude composition comprises extracting the crude composition with isopropyl alcohol (IPA).
14. A substrate structure, comprising: A resin layer; a conductive layer disposed on the resin layer; Including, The resin layer is formed from a resin composition using a crosslinking process, The resin composition comprises: 100 parts by weight of a hydrocarbon resin polymer; 0.01 to 50 parts by weight of a divinylaromatic compound; 2. A substrate structure comprising:
15. 15. The substrate structure of claim 14, wherein the crosslinking process does not use a triallylisocyanurate (TAIC) crosslinker.
Citation Information
Patent Citations
Heat-resistant porous resin multilayer substrate
JP2004087638A
Post curing resin composition and high frequency electrical insulating material using the same
JP2009161743A
Deionization module and electric device for producing deionized water
JP2010234358A
Post-curable resin composition and electrical insulating material using the same
JP2010280771A
Soluble polyfunctional vinyl aromatic copolymer, method for producing same, curable resin composition and cured product thereof
WO2018181842A1